North Dakota - Silverman, Robin Landew; Matusevich, Melissa N; Sand, Mary Reinertson (New York Children's Press, 2003)
Describes the geography, history, government, people, and tourist sights of North Dakota
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: North Dakota -- Juvenile literature; North Dakota